Analysis of verbal impoliteness in the speech acts of the defamation crime Acosta - Acuña - Reyes, Janeth (2023)
In some communicative situations, speakers use statements that, depending on the use of words, may be considered offensive or aggressive by their interlocutors; moreover, they could be classified as crimes against honor, according to the Peruvian Penal Code (amended in August 2021). This article analyzes nine statements evaluated in the crime of defamation made by Christopher Acosta Alfaro (CAA) to Cesar Acuña Peralta (CAP), with file number 03622-2021-0-1801-JR-PE-30, Lima-Peru (2022). For this purpose, the associative meanings according to the context are briefly considered. The aim of the study is to analyze the utterances as means of verbal discourtesy in relation to Fuentes' (2011) proposal and under the SPEAKING model proposed by Hymes (1962); likewise, to describe the speech acts that represent it. The results indicate that cotext, type of discourse, extralinguistic factors, evidentiality and intentionality play an important role in denominating utterances as defamatory. The research concludes that verbal discourtesy, in correspondence with speech acts in the crime of defamation, is expressed in attacks on job performance, values, intellect and interpersonal relationships, whose purpose is to damage, discredit and discredit the image of the other.